Student-staff partnership in India: A future possibility within contested terrain? - Vayada, Preeti (International Journal for Students as Partners, 2023)
Existing literature on named “students-as-partners” (SaP) practices suggest that these practices are still in their embryonic stage in Southeast Asia. In addition, the literature on SaP that supports it as a global practice has not examined the suitability of student partnership (SP) practices in Indian higher education (HE) yet. It is here that this paper seeks to contribute by examining Indian students with experiences in being a student partner in an Australian university to reflect on the challenges and possibilities in relation to implementing these practices in Indian HE. Adopting a postcolonial theoretical frame, this paper examines empirical evidence from an informal group discussion among six Indian collaborators. The data, analysed using a reflexive thematic analysis suggested by Braun and Clarke (2019), provide four interrelated themes that focus on the suitability of these practices in India intertwined with the inherent challenges. The study argues in favour of context-specific adaptation of the practice. Through the Indian students’ experiences, it adds to the ongoing conversations about knowing and understanding SaP in new ways and about positioning students as knowledgeable individuals, which is at the core of partnership practices. By bringing the voices of Indian students to the fore, this article argues in favour of embodying SaP as culturally relevant or a decolonising practice.